The application of post conference on shift operates in ward 16 and ward 21 Hospitals Mubarak Al-Kabir Kuwait - Ukar, Martin Muslih (South East Asia Nursing Research, 2022)
Post-conference is a discussion of the clinical aspects after implementing nursing care for patients. The results of observations and pretest with the nurses in the Ward 16 and Ward 21 Hospitals Mubarakiyah Al-Kabir Kuwait, the implementation of post-conferences was not optimal, because it was not in accordance with the rules of post-conference activities. This influences the nursing care provided by nurses. The purpose of this study was to optimize the implementation of the post-conference in room Ward 16 and ward 21 Hospitals Mubarakiyah Al-Kabir Kuwait in 2022. The study was conducted on 26 August 2022. The number of research samples was 7 team leaders in two rooms, 3 team leaders from Ward 16 and 4 team leaders from Ward 2, data collection was obtained through observations and questionnaires. After the implementation of nursing, the dissemination of knowledge and the application of role play about post conferences for 5 days showed the results of observation after science dissemination and role play showed an increase in nurses in implementing post conferences in ward 16 and ward 21 hospitals Mubarakiyah Al-Kabir Kuwait. The application of post-conference is very effective to improve the quality of shift operations in the room for this reason, it is expected that the hospital can follow the standard operating procedures in shift operations.